Evaluating The Knowledge of The Text Subject (History and Philosophy of Physical Education) Which is Studied by Students of College of Physical Education, First Grade Students in Mosul University - Abdullah, Alaa (Journal of Physical Education, 2010)
The study aimed at evaluating the knowledge of the text subject "The History and The Philosophy of Physical Education" Which is studied by students of College of Physical Education. It also aimed at identifying the scope in which the percentage of knowledge increases, and the researcher hypothesized that there is a high level of philosophical and historical knowledge. In addition, the level of knowledge of the individuals of the sample under study varies according to the variability of the scopes. The researcher used the questionnaire as a means for collecting data. The sample of the study consisted of students of college of Physical Education-First Grade and they were 225 students. The researcher used the arithmetical mean, standard deviation, centesimal weight, simple correlative coefficient, and discrepancy analysis (T) as means for collecting data. The researcher found that there is a good level of historical and philosophical knowledge .